Effect of eight weeks low intensity aerobic exercise on endothelin-1 plasma level, blood pressure and heart rate in healthy people and patients with coronary artery disease - Amin Mehrabi; Farhad Daryanoosh; Maryam Amirazodi; Mohammad Ali Babaee Baigi; Kouros Divsalar (Islamic Azad University, 2015)
Introduction: Cardiovascular homeostasis such as tonicity of vessels and blood flow can be affected by activities and hormones. The purpose of the present study was to investigate the effect of 8 weeks low intensity aerobic exercise on plasma endothelin-1 (ET-1), blood pressure and heart rate (HR) in healthy men and women and coronary artery disease (CAD) patients. Methods: In this quasi-experimental study, the experimental group consisted of 30 CAD patients (15 males and 15 females). The control group included 15 healthy males and 15 healthy females. These groups were chosen randomly. Participants did aerobic exercises with the intensity of 30%-40% of maximum HR. Blood samples were taken from participants in three stages (before, immediately and 24 hours after 8 weeks of exercise) and ET-1 plasma level was measured by ELISA method. Results: There was no significant alteration in ET-1 plasma level during the experiment. However, there was a significant difference in the systolic blood pressure (SBP) at the three stages in all groups (P = 0.01). In addition, we could observe a significant difference in the diastolic blood pressure (DBP) at the three stages in CAD men and healthy women (P = 0.03). Conversely, no significant difference was observed in the DBP of other groups. There was a significant difference in the blood pressure of three groups (P = 0.002) except for healthy men. Conclusion: The results demonstrated that, as there is a threshold in terms of time or intensity to stimulate the secretion of hormone; when the intensity and duration of exercise is below the stimulation threshold, no significant change can be observed in the level of ET-1.